Microbiological quality of ready-to-eat tilapia - Norfatin Mat (2015)
Ready-to-eat (RTE) food safety is an important issue. Inappropriate handling of RTE foods can cause food-borne outbreaks. This study was conducted to determine the microbiological quality of RTE tilapia obtained from food premises around Jeli area. The preliminary study include enumeration of total microbial load of respective samples using total plate count (TPC). Besides, total Staphylococcus count, total coliform and E. cob count, and total Salmonella count were also determined as a measurement on how each RTE tilapia in Jeli performed. All the enumeration procedure was done accordingly to the Bacteriology Analysis Manual (BAM) standard. Overally, the TPC of all samples obtained from Jeli was in the range of 1.50 + 2.12 to 5.98 + 0.08 log CFU/g and sample I (UMK cafe 2) recorded as the highest microbial load (5.98 ± 0.08 log CFUIg). The highest microbial load of total Staphylococcus count was in the range of 6.21 ± 0.04 log CFU/g and all the tested sample were identified as a non-pathogenic Staphylococcus. Meanwhile, the highest count for total coliform and E. coli was less than 1100 MPN/g. Among all the tested samples, 4 samples (B, D, G, H) were confirmed as a potential pathogenic E. coli species while 2 samples (E, F) were confirmed as non-pathogenic E.coli species. However, the total Salmonella count were not detected in this study. Most of the TPC samples (8 samples) were satisfactory and 1 sample was acceptable while for total Staphylococcus count, 6 samples were satisfactory, 2 samples (unsatisfactory) and 1 sample was unacceptable if compared to standard guidelines. Besides, the total coliform and E. coli count showed that 6 samples were satisfactory, 1 sample was acceptable and 2 samples were unsatisfactory. No Salmonella detected in this study (satisfactory). Based on these results, future study will be emphasized to determine the effect of taking RTE sample at different preparation or serving time.